2016
DOI: 10.1080/13648470.2016.1184009
|View full text |Cite
|
Sign up to set email alerts
|

Albinism, stigma, subjectivity and global-local discourses in Tanzania

Abstract: Societal ideas and explanations of albinism at the local level in Tanzania are conceived in terms of family history, social relations, economic status, moral-religious positions, global-local flows of information and humanitarian actions on behalf of people with the congenital condition. This paper aims to show how the subjectivities of people with albinism in Tanzania are shaped and re-shaped through local moral conceptions as well as globalizing (bio)medical explanations of albinism. An exemplary case study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
30
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 39 publications
3
30
0
2
Order By: Relevance
“…Perceived social support partially mediated the relationship between social stigma and subjective well‐being. Our results seem consistent with those of Brocco (), who reported that stigma and other marginalising behaviours negatively impacted the subjective well‐being of PWA in Tanzania.…”
Section: Discussionsupporting
confidence: 93%
“…Perceived social support partially mediated the relationship between social stigma and subjective well‐being. Our results seem consistent with those of Brocco (), who reported that stigma and other marginalising behaviours negatively impacted the subjective well‐being of PWA in Tanzania.…”
Section: Discussionsupporting
confidence: 93%
“…Although social models of disability are predominately used in Western definitions of disability, Brocco argues that the definition of being a disabled person may constitute a way for PWA to find alternative and more suitable epistemologies for albinism than some of the dominant negative discourses [ 22 ]. He argues that adopting a disability definition may help PWA explain to others why they cannot do certain activities such as working outdoors – ‘impairment effects’.…”
Section: Discussionmentioning
confidence: 99%
“…Myths and superstitions, fuelled by a lack of understanding surrounding albinism and the visible difference in the appearance of PWA can lead to stigmatisation, rejection, a lack of acceptance, perceptions of difference and limited social integration [ 1 , 22 , 25 ]. Their visible difference is so stark that they are in effect viewed as white people within a black community.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in Tanzania albinism is misbelieved to be the result of a curse [ 14 ] or because a pregnant woman has looked at a person with albinism [ 16 ]. Other authors too, have explored the articulation in society that albinism is God’s will [ 11 , 17 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%